Strategic orchestration in sharing economies: A configurational analysis of platform differentiation and governance alignment - Feifei Shao; Nianxin Wang (PLoS ONE, 2025)
Platform firms in the digital economy face a critical challenge: balancing differentiation-driven competitive strategies with the need for institutional legitimacy. While existing research recognizes this tension, current frameworks inadequately address how governance mechanisms mediate strategic positioning in trust-sensitive sharing economy contexts. This study integrates Porterian positioning theory with platform boundary theory to analyze 33 chinese sharing platforms through fuzzy-set Qualitative Comparative Analysis (fsQCA), examining configurations of three external positioning dimensions (variety-based, gender-based, and region-based differentiation) and two internal governance dimensions (resource ownership and transaction process differentiation). Our analysis identifies two equifinal success pathways: (1) An aggressive strategy combining market pioneering in user segmentation with cautious transaction governance, and (2) a conservative strategy aligning geographic specialization with institutional compliance in resource ownership. Both pathways demonstrate that governance mechanisms compensate for the legitimacy risks inherent in differentiation strategies, with platform performance contingent on strategic coherence between external positioning and internal governance architectures. Three key theoretical advances emerge: First, integrating Porterian positioning theory with platform boundary theory, we demonstrate how governance dimensions serve as compensatory tools that enable radical market differentiation in sharing economy platforms without legitimacy erosion, a trade-off insufficiently addressed in prior distinctiveness theory research. Second, building on configuration theory, in the context of the sharing economy, we solve the theoretical tensions in the distinctiveness-performance relationship by demonstrating configurational equifinality—both radical and conservative strategies succeed when external and internal dimensions achieve strategic coherence. Third, advancing research of sharing user participation, we establish that participation in trust-sensitive sharing platforms depends on strategic alignment between positioning and governance dimensions rather than isolated optimization of individual dimensions. These contextualized findings provide managers with evidence-based frameworks to coordinate market positioning strategies with governance investments, particularly when operating in institutionally complex environments. The demonstrated mechanisms in China’s sharing economy warrant future verification in other platform types and cultural contexts.